The discourse on development in the Latin American and Caribbean Interreligious Alliance for the 2030 Agenda for Sustainable Development: An Analysis from the Device - Sánchez, Gina Marcela Reyes; Posada, Jorge Eliécer Martínez (Journal of Posthumanism, 2025)
This paper examines the configuration of Faith-Based Organizations (FBOs), with a particular focus on the Latin American and Caribbean Interreligious Alliance (AILC), as a device for the administration of the development statement proposed by the 2030 Agenda. The hypothesis advanced in this study is that the AILC functions as a conduit for the implementation and administration of power relations and strategies associated with the discourse on sustainable development proposed by the 2030 Agenda. This discourse is understood as a transformative event, i.e. a shift in the relations of force that will catalyze and nurture capitalist development.